SOCIAL CAPITAL DALAM KEWIRAUSAHAAN LOKAL, KAJIAN KETERLIBATAN MASYARAKAT DALAM PARIWISATA DI DELHA, KAB. ROTE NDAO, NUSA TENGGARA TIMUR - Fitri Ciptosari; Titi Susilowati Prabawa; Antonius Bele (Jurnal Kawistara, 2019)
Entrepreneur is believed as the backbone of the economy. Very few studies in NTT, and none in Rote, have explored this area in the context of tourism. Based on ethnographic research, this study focuses on local tourism entrepreneurship in the context of socio-cultural complexities of Delha’s community, Rote. This qualitative research aimed to discusses how local entrepreneurs respond to every opportunity and challenge, due to cultural remoteness of host communities to tourism-related business. Data were collected with observations and in depth interview with life history approach. The findings show that social capital has been utilized by the local entrepreneur in responding to every opportunity and challenge. Bonding social capital has a large role at start up, while bridging social capital provides wider outside networks to maintain and develop bigger business. In this study, linking social capital has found very limited. Even though linking social capital plays an important role in supporting capital supports, business licenses, and other facilities that help a lot in business development. Given the literature, this is not a mainstream result, kinship and solidarity as a form of social capital does not always support the entrepreneurial process, particularly in the context of communal society. As a recommendation, the culture of collectivity that developed strongly in Delha community can be utilized as social capital in developing socio-enterprise.